Gender differences in anger expressions among secondary students - Nor Shafrin Ahmad; Rahimi Che Aman; Ahmad Zamri Khairani (Institute of Advanced Engineering and Science, 2021)
Individuals with choleric temperaments easily get angry and can be problematic if not expressed appropriately. The purpose of this study was to identify gender differences in anger expressions among secondary school students. Respondents were secondary school students in four states in the Northern region of Malaysia. A total of 3348 students were involved, including 1,800 males and 1,548 females. Respondents aged between 13 and 16 were randomly selected from 20 secondary schools. Descriptive analyses and t-test were used to identify anger expressions among secondary school students. Findings showed that 780 respondents agreed that they are hot-tempered, while 2568 others did not. From the 780 hot-tempered respondents, 370 are males and 410 are females. A total of 3160 from the 3348 respondents did not meet their school counsellors for counselling sessions when they had anger problems. The findings also revealed a significant difference in four types of anger expressions between male and female students. They were in aggressive, verbal, intrinsic anger expression, and intrinsic anger control. The findings revealed that school counsellors need to equip students with specific, creative, and innovative interventions to cope with different anger expression.